Development of a Virtual Reality Nursing Assistance System to Positively Enhance Rectal Medication Adherence in Children (International Journal of Nursing Education, 2022)
Children may feel uneasy, anxious and fearful when faced with an invasive procedure because they cannot understand the reason for their illness and they fear the destruction of the integrity of their bodies. In rectal drug delivery (the use of anal suppositories), children often move their hips and cry during the procedure, which may cause the suppository to inadvertently break, slip out, or be misplaced in the vagina. In order to find to a solution to the clinical issue, this study focuses on the application of virtual reality in developing a VR nursing assistance system that can be used in clinical practice with only ordinary cell phones and simple VR headsets, called “Little Hero Saves the Earth”. This system allows children to immerse themselves in the plot of a story through a first-person perspective (as the “little hero”). When the little hero needs to have the superpower rocket fitted (what the child perceives in the first-person perspective), the nurse places the child in a side-lying position before inserting the suppository (superpower rocket) in sync with the plot. This serves to reduce the child’s fear of invasive procedures, encourage the child to think of anal suppositories in a positive way, and lead to a sense of autonomy and accomplishment in the child, thus creating a positive, successful experience.
Keywords: virtual reality, nursing assistance system, rectal drug delivery, anal suppository, anxiety, fear.